2003
DOI: 10.1002/pmic.200300467
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the activity and identification of enzymes after separation of cytosol proteins in mouse liver by microscale nondenaturing two‐dimensional electrophoresis

Abstract: Enzyme activities such as of fructose bisphosphatase, malate dehydrogenase and carbonic anhydrase were analyzed after cytosol proteins in the mouse liver and were separated using nondenaturing two-dimensional electrophoresis (2-DE). The activities of both fructose bisphosphatase and malate dehydrogenase were inhibited by thyroxine, and fructose bisphosphatase activity was specifically inhibited by adenosine monophosphate in nondenaturing 2-DE. Furthermore, polypeptides of the separated proteins were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Hydrolytic activity of the esterase on the membrane (spot 1) was approximately 20% of the original activity of the tissue homogenate when the hydrolytic activity of the esterase was measured as a quantitative assay using a-naphthyl acetate and Fast violet B salt. We previously showed that cytosolic enzymes are separated by non-denaturing 2-DE (Shimazaki et al 2003). So, many enzymes separated by this method and stained with imidazole and zinc salts can be transferred and immobilized on membranes without impairing their activities by this method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolytic activity of the esterase on the membrane (spot 1) was approximately 20% of the original activity of the tissue homogenate when the hydrolytic activity of the esterase was measured as a quantitative assay using a-naphthyl acetate and Fast violet B salt. We previously showed that cytosolic enzymes are separated by non-denaturing 2-DE (Shimazaki et al 2003). So, many enzymes separated by this method and stained with imidazole and zinc salts can be transferred and immobilized on membranes without impairing their activities by this method.…”
Section: Resultsmentioning
confidence: 99%
“…Sucrose was added to the liver cytosolic fraction at 40% (w/v). Proteins in the cytosolic fraction (100-300 lg) were subjected to microscale non-denaturing 2-DE by the method of Shimazaki et al (2003). First dimensional isoelectric focusing (IEF) was performed on rod gels (35 mm 9 1.3 mm ID) containing 4% (w/v) acrylamide, 0.2% (w/v) bisacrylamide, 2% (v/v) ampholine pH 3.5-10, 1% (v/v) ampholine pH 3.5-5, 0.05% ammonium persulphate and 0.029% (v/v) N,N,N 0 ,N 0 -tetramethylenediamine.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins in each sample (100-500 mg) were subjected to microscale non-denaturing 2DE, as previously reported (Shimazaki and Manabe, 2005;Shimazaki et al, 2003Shimazaki et al, , 2004Shimazaki et al, , 2006. IEF was undertaken on rod gels (length, 35 mm; i.d., 1.3 mm) containing 4% acrylamide (0.2% Bis), 2% ampholine pH 3.5-10, 1% ampholine pH 3.5-5, 0.05% ammonium persulfate, and 0.029% N,N,N 0 ,N 0 -tetramethylethylene diamine (TEMED).…”
Section: Non-denaturing Electrophoresis and Electroblottingmentioning
confidence: 99%
“…Recently, we have reported that proteomic analysis involving enzyme activity is performed using non-denaturing 2DE and mass spectrometry (MS) (Shimazaki and Manabe, 2005;Shimazaki et al, 2003Shimazaki et al, , 2004Shimazaki et al, , 2006. However, as macromolecular substrates such as proteins cannot enter into the gel, it might be necessary for enzymes to be transferred to blotting membranes without impairing their activities after separation by non-denaturing 2DE.…”
Section: Introductionmentioning
confidence: 99%
“…LDH and carboxylesterase are identified after the enzymes obtained from mouse liver are separated by nondenaturing 2-DE 1,5 . Thus, when inhibitors, such as oxamate and acrinol, are allowed to interact with the enzymes in the non-denaturing gels, reversible inhibition of enzyme activity can be examined by nondenaturing 2-DE.…”
Section: Introductionmentioning
confidence: 99%